EFFECTIVENESS OF FRUIT JUICE AS COMPLEMENTARY THERAPY ON BLOOD PRESSURE OF HYPERTENSION PATIENTS : A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS - Mahendra, Bayu; Surudarma, I Wayan; Wihandani, Desak Made; Ruma, I Made Winarsa (E-Jurnal Medika Udayana; Vol 11 No 9 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i9.P17, 2022)
Hypertension treatment can be helped through complementary therapies, one of which is fruit juices. This study aimed to systematically review the evidence from various study regarding the effect of fruit juices on blood pressure in hypertensive patients and the types of fruit juices that are proven to be effective in reducing hypertension.This study is systematic review. Literature searching was conducted in four electronic databases, namely CINAHL, EMBASE, Pubmed, and Sciencedirect with the phrase fruit juices AND (hypertension OR blood pressure). Studies obtained from searching will be selected based on a screening title and abstract, eligibility criteria, and assesment risk of bias. The results of the study obtained 21 final studies with RCT research designs that passed the screening with complete eligibility criteria. However, the studies with valid results only amounted to 8 studies. These data show that as many as 5 studies prove fruit juices can reduce blood pressure in hypertensive patients and 3 other studies have stated the opposite. Thus, it can be concluded that there is strong evidence that fruit juices has a significant effect on reducing blood pressure in hypertensive patients. Fruit juices that have been shown to be effective are orange juice and queen garnet plum juice